International Tourism Demand and Macroeconomic Factors - Khandaker, Sarod; Islam, Silvia Zia (International Journal of Economics and Financial Issues, 2017)
The Global Financial Crisis (GFC) in the early 21st century curtailed international tourism growth, and the tourism industry suffered significantly during the financial crisis. There is evidence in the academic literature that the demand for international tourism declined significantly during the GFC and the impact remain consistent after the GFC. In this paper, we use several country level economic variables and find evidence that Political Stability and Exchange Rate volatility is negatively correlated with international tourism demand for our sample developed and emerging country group. Therefore, we conclude that the favourable Macroeconomic Policy, Governance Mechanisms and lower Exchange Rates are desirable for the growth of a tourist-based economy. Keywords: Tourism Income, .Exchange Rate, Global Financial Crisis (GFC), Macroeconomic Factors, Governance JEL Classifications: G14, G15